Penggunaan Media Chatbot dalam Model Pembelajaran Direct Instruction sebagai Upaya Meningkatkan Hasil Belajar Siswa - Fikri, Ely Khuzatul; Solihat, Ai Nur; Aisyah, Iis (Global Education Journal, 2023)
This study aims to investigate using chatbot media in the direct instruction learning model to improve student learning outcomes in economics subjects and using a quasi-experimental method with a quantitative approach. Data collection techniques used pretest and posttest in the form of multiple choice questions. The research population was all class X IPS SMAN 7 Tasikmalaya students, totaling 208 students. The sample was taken based on a purposive sampling technique, so class X IPS 5 was obtained as the experimental class and class X IPS 2 as the control class. Data analysis techniques used paired sample t-test and independent sample t-test with a significance level of 5% or 0.05. The results of the hypothesis testing show: (1) There is an increase in student learning outcomes in the experimental class with an average pretest score of 41.82 and a posttest score of 81.56. (2) There is an increase in student learning outcomes in the control class, with an average pretest score of 35.29 and a posttest average of 76.74. (3) There is a difference in the increase in learning outcomes in the experimental class and the control class, with a comparison of the n-gain average value of the experimental class being greater than that of the control class, equal to 0.69 and 0.63. So, using chatbot media in the direct instruction learning model can improve student learning outcomes.